Continuous Improvement : Alternatif Strategi Pondok Pesantren dalam Mempertahankan Eksistensinya di Era Post pandemic - Shinta Nisaus Syuroya (Progressive of Cognitive and Ability, 2022)
Pesantren is an Islamic educational institution that is also affected by the COVID-19 pandemic. To maintain its existence in the post-pandemic era, Islamic boarding schools need appropriate and fast strategies so as not to interfere with the vision and mission of the institution. With the right strategy, it is hoped that the quality of education in Islamic boarding schools will be maintained, and the public's trust will not be lost that pesantren is the center for studying religion. This research belongs to the type of qualitative research using the literature review method. The author uses data from previous research results and takes related concepts that are still related to the title, to be able to support the formulation of strategies that can be applied to Islamic boarding schools to maintain their existence in the post-pandemic era. The results of the study reveal that the theory of continuous improvement can be an alternative strategy that can be applied in Islamic boarding schools to improve the quality of the institution. The implementation of this strategy can be adjusted to the vision and mission of the Islamic boarding school so that the characteristics of the institution can still be a unique and distinct advantage. Keywords: strategy, pesantren, post pandemic, continuous improvement